Effect of Capital structure on share price : Listed companies in Sri Lanka. - Tharshiga, P.; Anandasayanan, S.; Subramaniam, V.A. (IJSSE Annual International Interdisciplinary Conference., 2014)
The capital structure of a company refers a combination of the long term used by the firms. The theory of capital structure is closely related to the firm’s cost of capital. The decision regarding to the capital structure or financial leverage is based on the objective of achieving maximization of shareholder’s wealth. Present study is an attempt to evaluate the effect of capital structure on share price in Sri Lankan Listed companies over the period of 2008 to 2012.Correlation analysis and regression analysis were used to analysis the relationship between Capital Structure and share price in listed companies in Sri Lanka. Analyzed results revealed that there were significant relationships between share price and capital structure.
Keywords: Capital structure; Share price